“Vamos falar de história?”: narrativas de golpe, negacionismos e falsificações do conhecimento histórico no Youtube - Rodrigues, Cinthia Raquel de França (2023)
This research to aims analyze the use YouTube as a space for disseminating narratives about the coup d'état that culminated in establishment civil-military dictatorship (1964-1985) in Brazil and how these can be problematized basic education. The proposal presented here starts from experiences in the classroom, in which study of this theme in Basic Education deals with students' narratives reflecting absorption manipulative explanations this historical event from the past and which continues today. Through the popularization videos that relativize, deny and continue to intentionally revise this event with clear political intentions, channel “Vamos Falar de História?” it produces narratives that romanticize the different media through which Brazilian society was affected by the state authoritarianism 21 years of the Dictatorship. Through study the relationship between Coup narratives, the History Present Time, Internet and Historical Consciousness, we seek to understand how several Coup narratives become popular and diverge from each other. With help of the concept historical awareness worked by Jörn Rüsen, the educational product proposal has as its basic presupposition to create didactic situations in which students can, together with their teachers, develop part scientific process historical construction through the development a pedagogical material, a didactic script created as suggestion a educational workshop for teachers of basic education, in order to be a tool for the classroom problematizing curriculum content about the Civil-Military Coup and using as a counterpoint denialist speeches, way to differentiate with the students “what is fact, what is fake”, promoting a reformulation in the presentation content to the students with a didactic perception making scientific history.